Seed size, endosperm and germination variation in sexual and apomictic Boechera - Paczesniak, Dorota; Pellino, Marco; Goertzen, Richard; Guenter, Devan; Jahnke, Siegfried; Fischbach, Andreas; Lovell, John T.; Sharbel, Timothy F. (Frontiers in Plant Science, 2022)
Asexual reproduction results in offspring that are genetically identical to the mother. Among apomictic plants (reproducing asexually through seeds) many require paternal genetic contribution for proper endosperm development (pseudogamous endosperm). We examined phenotypic diversity in seed traits using a diverse panel of sexual and apomictic accessions from the genus Boechera. While genetic uniformity resulting from asexual reproduction is expected to reduce phenotypic diversity in seeds produced by apomictic individuals, pseudogamous endosperm, variable endosperm ploidy, and the deviations from 2:1 maternal:paternal genome ratio in endosperm can all contribute to increased phenotypic diversity among apomictic offspring. We characterized seed size variation in 64 diploid sexual and apomictic (diploid and triploid) Boechera lineages. In order to find out whether individual seed size was related to endosperm ploidy we performed individual seed measurements (projected area and mass) using the phenoSeeder robot system and flow cytometric seed screen. In order to test whether individual seed size had an effect on resulting fitness we performed a controlled growth experiment and recorded seedling life history traits (germination success, germination timing, and root growth rate). Seeds with triploid embryos were 33% larger than those with diploid embryos, but no average size difference was found between sexual and apomictic groups. We identified a maternal effect whereby chloroplast lineage 2 had 30% larger seeds than lineage 3, despite having broad and mostly overlapping geographic ranges. Apomictic seeds were not more uniform in size than sexual seeds, despite genetic uniformity of the maternal gametophyte in the former. Among specific embryo/endosperm ploidy combinations, seeds with tetraploid (automomous) endosperm were on average smaller, and the proportion of such seeds was highest in apomicts. Larger seeds germinated more quickly than small seeds, and lead to higher rates of root growth in young seedlings. Seed mass is under balancing selection in Boechera, and it is an important predictor of several traits, including germination probability and timing, root growth rates, and developmental abnormalities in apomictic accessions.